Binding mode of Pyridoclax to myeloid cell leukemia-1 (Mcl-1) revealed by nuclear magnetic resonance spectroscopy, docking and molecular dynamics approaches. Issue 14 (21st September 2020) - Bourafai-Aziez, A.; Sebban, M.; Benabderrahmane, M.; Marekha, B.; Denis, C.; Paysant, H.; Weiswald, L. B.; Carlier, L.; Bureau, R.; Coadou, G.; Ravault, D.; Voisin-Chiret, A. S.; et al.
Abstract: Myeloid cell leukemia-1 (Mcl-1) is an anti-apoptotic member of the Bcl-2 family proteins. Its amplification is one of the most frequent genetic aberrations found in human cancers. Pyridoclax, a promising BH3 mimetic inhibitor, interacts directly with Mcl-1 and induces massive apoptosis at a concentration of 15 µM in combination with anti-Bcl-xL strategies in chemo-resistant ovarian cancer cell lines. In this study, a combined experimental and theoretical approach was used to investigate the binding mode of Pyridoclax to Mcl-1. The representative poses generated from dynamics simulations compared with NMR data revealed: (i) Pyridoclax bound to P1 and P2 pockets of Mcl-1 BH3 binding groove through its styryl and methyl groups establishing mainly hydrophobic contacts, (ii) one of the ending pyridines interacts through electrostatic interaction with K234 side chain, a negatively charged residue present only in this position in Mcl-1. Communicated by Ramaswamy H. Sarma